Effects of Exhaust Gas Recirculation (EGR) on a Diesel Engine Fuelled with Palm-Biodiesel - Mohd Hafizil, Mat Yasin; R., Mamat; Ahmad Fitri, Yusop; Perowansa, Paruka; Talal, Yusaf; G., Najafi (Elsevier Ltd, 2015)
Increasing global population in present years means more vehicle ownership which leads to the increasing of oxides of nitrogen (NOx) and greenhouse gas emission. Oxides of nitrogen (NOx) are produced from the fuels which burned at high temperatures; contributes to the formation of ozone smog, harmful unseen particles, acid rain, and oxygen depletion that reduced the water quality. The use of higher oxygenated nature biodiesel as an alternative fuel also contributes to the increasing formation levels of NOx emission. In respond to the matters arise, exhaust gas recirculation (EGR) has been introduced to control NOx emissions from diesel engines effectively which lowers the oxygen concentration in the combustion chamber. In this paper, an experimental study was conducted on a Mitsubishi 4D68 four stroke, water cooled DI diesel engine fuelled with neat palm-biodiesel operating with diaphragm exhaust gas recirculation (EGR). Both biodiesel fuel and EGR are employed together to evaluate the engine performance and exhaust emission particularly NOx content. Tests were performed under a steady state condition where conventional diesel fuel was used as a baseline fuel. According to the experimental results, diesel engine operating with palmbiodiesel and EGR reduced the brake power output, decreased the engine torque, increased fuel consumption, decreased NOx and absolute slight increment in other emissions include CO2, CO, and particulate matters.